An Efficient Class of Dual to Product-Cum- Dual to Ratio Estimators of Finite Population Mean in Sample Surveys (Global Journal of Science Frontier Research, 2012)
This paper considers a class of dual to product-cum-dual to ratio estimators for estimating finite population mean of the study variate using auxiliary variate. The bias and mean square error of the proposed estimator have been obtained. The asymptotically optimum estimator (AOE) in the class has also been identified along with its approximate bias and mean square error. Theoretical and empirical studies have been done to demonstrate the superiority of the proposed estimators over the other estimators.
Keywords: Finite population mean; Auxiliary variate; Dual to product-cum-dual to ratio estimator; Mean square error; Efficiency